Artificial intelligence-based, non-invasive assessment of the central aortic pressure in adults after operative or interventional treatment of aortic coarctation - Renate Oberhoffer; Peter Ewert; Harald Kaemmerer; Nicole Nagdyman; Oliver Dewald; Frank Klawonn; Michael Huntgeburth; Andreas Eicken; Christian Meierhofer; Sebastian Freilinger; Martin Middeke; Pinar Bambul Heck; et al. (Open Heart)
Background Aortic coarctation (CoA) is a congenital anomaly leading to upper-body hypertension and lower-body hypotension. Despite surgical or interventional treatment, arterial hypertension may develop and contribute to morbidity and mortality. Conventional blood pressure (BP) measurement methods lack precision for individual diagnoses and therapeutic decisions. This study evaluated the use of artificial intelligence-based pulse wave analysis (AI-PWA) to assess central aortic blood pressure (CABP) and related parameters in post-treatment CoA patients.Methods This exploratory, cross-sectional study enrolled 47 adults with CoA, between June 2023 and May 2024. Peripheral BP (PBP) was conventionally measured, and CABP was assessed using the VascAssist2 (inmediQ, Butzbach, Germany). Hypertension was defined by systolic BP≥140 mm Hg and/or diastolic BP≥90 mm Hg for PBP. Using AI-PWA, patients with systolic CABP≥130 mm Hg and/or diastolic BP≥90 mm Hg were classified as hypertensive.Results The study cohort’s age was 41.5±13.7 years, with all patients having undergone previous aortic surgery or intervention. PBP measurements showed a systolic BP of 135.4±14.4 mm Hg at the upper and 147.8±20.3 mm Hg at the lower extremities. CABP measurements were significantly lower, with a systolic BP of 114.3±15.8 mm Hg (p<0.001). Overall, 32 patients (68.1%) were diagnosed as hypertensive, either by PBP measurement (n=13/27.7%), because of antihypertensive treatment (n=9; 40.4%), or a combination of both. The measurement of PBP was more likely to indicate arterial hypertension than the measurement of CABP (n=12; 25.5% vs n=4; 8.5%). Pulse wave velocity, indicative of aortic stiffness, averaged 9.1 m/s, with higher values in 13 patients (27.7%), including 4 after end–end anastomosis, 2 after graft interposition and 7 after stent placement/angioplasty as the most recent procedure. An increased augmentation index as an indicator of arterial stiffness was observed in nine patients (19.1%). Comparing PBP and CABP in the entire collective, significant differences were found for CABP in relation to the procedure performed, with higher values in patients after prosthesis interposition as their last treatment (p<0.05).Conclusion AI-PWA provides valuable insights into cardiovascular stress in CoA patients, beyond PBP measurements. The study highlights the need to incorporate CABP measurements into clinical practice to avoid overdiagnosis of hypertension. Further research with larger cohorts is needed to validate these findings and refine management strategies for CoA patients.